A randomized, controlled, double-blind crossover study on the effects of 2-L infusions of 0.9% saline and plasma-lyte® 148 on renal blood flow velocity and renal cortical tissue perfusion in healthy volunteers - Chowdhury, Abeed H; Cox, Eleanor F; Francis, Susan T; Lobo, Dileep N (Annals of surgery, 2012)
We compared the effects of intravenous infusions of 0.9% saline ([Cl] 154 mmol/L) and Plasma-Lyte 148 ([Cl] 98 mmol/L, Baxter Healthcare) on renal blood flow velocity and perfusion in humans using magnetic resonance imaging (MRI). Animal experiments suggest that hyperchloremia resulting from 0.9% saline infusion may affect renal hemodynamics adversely, a phenomenon not studied in humans. Twelve healthy adult male subjects received 2-L intravenous infusions over 1 hour of 0.9% saline or Plasma-Lyte 148 in a randomized, double-blind manner. Crossover studies were performed 7 to 10 days apart. MRI scanning proceeded for 90 minutes after commencement of infusion to measure renal artery blood flow velocity and renal cortical perfusion. Blood was sampled and weight recorded hourly for 4 hours. Sustained hyperchloremia was seen with saline but not with Plasma-Lyte 148 (P < 0.0001), and fall in strong ion difference was greater with the former (P = 0.025). Blood volume changes were identical (P = 0.867), but there was greater expansion of the extravascular fluid volume after saline (P = 0.029). There was a significant reduction in mean renal artery flow velocity (P = 0.045) and renal cortical tissue perfusion (P = 0.008) from baseline after saline, but not after Plasma-Lyte 148. There was no difference in concentrations of urinary neutrophil gelatinase-associated lipocalin after the 2 infusions (P = 0.917). This is the first human study to demonstrate that intravenous infusion of 0.9% saline results in reductions in renal blood flow velocity and renal cortical tissue perfusion. This has implications for intravenous fluid therapy in perioperative and critically ill patients. NCT01087853.